A primazia da vontade sobre a razão em schopenhauer - Pereira, Fernando Vinícius Mendes (2017)
The purpose of our dissertation is to show in Schopenhauer's philosophy that there is a predominance of Will over intellectual activities, and that in this way we see Reason staying in the background, being one of the contingent means of survival of the species. Thus, we chose to work, mainly, with three pieces of work by Schopenhauer. We will begin our investigation with an analysis of the text "Critique of Kantian philosophy" of 1819, such text is an appendix of the first book of The world as Will and Representation; Then we will have as main source the Second Book of "The world as Will and Representation", also of 1819; And finally, we will work with the text entitled On Will in Nature, of 1836. With the "Critique of Kantian philosophy", we will show that Schopenhauer accepts in Kant's philosophy the separation between the phenomenon and the thing itself, thus establishing a limit for knowledge. On the other hand, the Critique demonstrates all the fragility of the Kantian Reason, making a metaphysics in the most traditional sense impossible. Therefore, Schopenhauer proposes, then, the search for a metaphysics also on the ground of experience, on the ground of empirical intuition, through a certain point, already mentioned previously. This one point, as we shall see, is the body itself. The body here assumes the role of mediator, it is the form that we can connect the knowledge of the external experience with the knowledge of the inner experience. It is through the body that Schopenhauer will announce the Will as a metaphysical essence. The analysis of the concept of Will is then our next step: where we show that it is the metaphysical foundation of all beings, being Una, free and irrational. And their irrationality, or blindness, creates the conflict that is present in all phenomena and is the condition of their existence. The condition of the existence of all phenomena is thus, the theme of our last chapter, where we will show how Reason is to Schopenhauer a mere brain activity: he separates, in a radical way, Will and Reason, putting Will as the vital principle of all beings and Reason as mere brain function. In this way, Schopenhauer puts the Reason as a physiological activity, being the mere will to know objectified. Therefore, we can say that the Schopenhaurian system places all beings under the same roof: the roof of the primacy of Will.